Regulation of PrPC signaling and processing by dimerization - Roucou, Xavier (Frontiers in Cell and Developmental Biology, 2014)
The cellular prion protein (PrPC) is a glycosylphosphatidylinositol (GPI)-anchored protein present at the cell surface. PrPC N-terminal moiety is intrinsically disordered and is able to interact with a variety of ligands. Physiological ligands have neurotrophic activity, whilst others, including protein toxic oligomers, have neurotoxic functions. These two opposite activities involve different interacting partners and result from different PrPC-activated signaling pathways. Remarkably, PrPC may be inactivated either by physiological endoproteolysis and release of the N-terminal domain, or by ectodomain shedding. Ligand-induced PrPC dimerization or enforced dimerization of PrPC indicate that PrPC dimerization represents an important molecular switch for both intracellular signaling and inactivation by the release of PrPC N-terminal domain or shedding. In this review, we summarize evidence that cell surface receptor activity of PrPC is finely regulated by dimerization.